Identification of fish CMPK2 as an interferon stimulated gene against SVCV infection. Issue 92 (September 2019) - Liu, Wanmeng; Chen, Bo; Chen li; Yao, Jian; Liu, Jiaoyun; Kuang, Ming; Wang, Fang; Wang, Yeda; Elkady, Gehad; Lu, Yuanan; Zhang, Yongan; Liu, Xueqin
Abstract: Cytidine/uridine monophosphate kinase 2 (CMPK2) is known as a nucleoside monophosphate kinase in mitochondria to maintains intracellular UTP/CTP, and could be induced by immunostimulants LPS and Poly (I:C) in mammals, suggesting its potential antiviral and antibacterial role. In this study, CMPK2 was cloned and characterized in Fathead minnow (FHM) cells. In vivo analysis of tissue distribution revealed that CMPK2 transcript was detected in all the tissues of zebrafish ( Danio rerio ) examined in this study, particularly abundant in liver, spleen and kidney. In addition, indirect immunofluorescence showed that CMPK2 was localized in the cytoplasm of FHM cells. Expression of CMPK2 mRNA was significantly up-regulated following challenge with Spring viraemia of carp virus (SVCV), poly(I:C), or zebrafish IFN1 and IFN3 both in vitro and in vivo . Furthermore, overexpression and RNA interference of CMPK2 in SVCV-infected FHM cells showed significantly antiviral effect. In summary, this study for the first time shows the presence and distribution of CMPK2 in different tissues of zebrafish, but also demonstrates its antiviral potential against SVCV infection in vivo . These new findings could contribute to explain the molecular mechanism of the CMPK2 mediated antiviral function. Highlights: CMPK2 was cloned and characterized in Fathead minnow (FHM) cells. CMPK2 was identified as an Interferon Stimulated Gene in fish for the first time. Overexpression and RNA inference of CMPK2 in SVCV-infected FHM cells showed significantly antiviral effect.